Key Performance Indicators in Higher Education: A Systematic Review of the Conceptualization, Dimensions, Frameworks, and Challenges of KPIs - Teshome, Samson Worku (Darul Yasin Al Sys, 2025)
Key Performance Indicators (KPIs) have emerged as critical tools for measuring and improving the performance of higher education institutions (HEIs). This systematic literature review synthesizes existing research on the conceptualization, implementation, frameworks, and challenges associated with KPIs in the higher education sector. Following the PRISMA framework, a comprehensive search was conducted across major academic databases, including Google Scholar, ERIC, PubMed, ProQuest, and Scopus, resulting in the selection of 20 relevant studies published between 1992 and 2024. The review identifies key dimensions of KPIs, such as academic performance, research productivity, and institutional efficiency highlighting their broad applicability. However, it also uncovers persistent challenges in implementation, including issues related to data reliability, stakeholder resistance, and the difficulty of aligning KPIs with diverse institutional goals. The study concludes that while KPIs are widely recognized as valuable performance management tools, there is a pressing need for more standardized frameworks and the integration of advanced technologies to improve the accuracy and utility of KPI systems. This review contributes to the discourse on higher education management by offering a comprehensive overview of current KPI practices and proposing directions for future research and institutional policy development.